2021
DOI: 10.3390/su13042361
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning: An Underlying Mechanism of Age and Gender Differences in Self-Assessed Risk Tolerance among an Aging Population

Abstract: Attitude toward risk plays a vital role in an individual’s financial decision-making and well-being. Past studies have found significant association of age and gender with risk tolerance. However, studies on the factors affecting the underlying mechanism are scant. The purpose of this research is to test whether cognitive functioning mediates the association between age, gender, and self-assessed risk tolerance. Using the 2014 wave of the Health and Retirement Study, path analysis was conducted to test the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…For several decades, risk tolerance was primarily assessed via an individual's financial portfolio, calculated as a proportion of a persons' risky assets to their total wealth. While one study found that older adults were less risk averse than younger adults, that is, an increased risk tolerance (Wang & Hann, 1997), the majority of studies find that older adults actually show a decreased risk tolerance, as shown by a lower proportion of risky assets (Pålsson, 1996;Jianakoplos & Bernasek, 2006;Bonsang & Dohmen, 2015;Sharma and Chatterjee, 2021). This relationship between financial risk tolerance and age has been shown to be mediated by cognitive ability, suggesting that agerelated change in cognition may be an integral component of this relationship (Bonsang & Dohmen, 2015;Sharma & Chartterjee, 2021).…”
Section: Risk Tolerancementioning
confidence: 99%
“…For several decades, risk tolerance was primarily assessed via an individual's financial portfolio, calculated as a proportion of a persons' risky assets to their total wealth. While one study found that older adults were less risk averse than younger adults, that is, an increased risk tolerance (Wang & Hann, 1997), the majority of studies find that older adults actually show a decreased risk tolerance, as shown by a lower proportion of risky assets (Pålsson, 1996;Jianakoplos & Bernasek, 2006;Bonsang & Dohmen, 2015;Sharma and Chatterjee, 2021). This relationship between financial risk tolerance and age has been shown to be mediated by cognitive ability, suggesting that agerelated change in cognition may be an integral component of this relationship (Bonsang & Dohmen, 2015;Sharma & Chartterjee, 2021).…”
Section: Risk Tolerancementioning
confidence: 99%
“…More specifically, financial risk tolerance can be defined as a person’s willingness to engage in a financial behaviour in which the outcomes are both unknown and potentially negative [ 23 ]. Undoubtedly, attitude toward risk has an impact on an individual’s economic decisions in different contexts [ 6 ]—consumption, savings, investments, etc.—and plays a vital role in the individual’s well-being [ 24 ]. Specifically, financial risk tolerance plays a key role in shaping decisions on how to allocate financial assets (e.g., [ 12 , 23 , 25 ]) and, consequently, financial decisions should be in accordance with the risk tolerance of individuals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quando adicionado o termo constante estimado para a regressão múltipla ao termo beta, percebe-se que a raça branca possui um nível de tolerância ao risco igual a 3 (moderado) o que coaduna com os achados de Yao et al (2005) que mencionam que pessoas da raça branca possuem maior tolerância ao risco. Aqui cabe uma observação que diz respeito a forte miscigenação do povo brasileiro, que carece ainda de estudos mais aprofundados, dado que em diversos estudos reportados na literatura (Rabani et al 2020;Sharma & Chatterjee, 2021), a raça negra tem mais tolerância ao Risco do que a raça branca, principalmente com populações relacionadas a países africanos, cuja realidade socioeconômica é muito semelhante com a realidade dos negros no Brasil, o que distingue-se em algum grau da amostra coletada.…”
Section: R C Aunclassified